PSYCHOPREVENTIVE PRINCIPAL APPROACHES TO PREVENTING INFORMATION THREATS AMONG YOUTH - Hayitova H.M. (PT. Antis International Publisher, 2024)
The rapid expansion of digital information has heightened the vulnerability of young people to various information threats, necessitating effective prevention strategies. General Background: In an increasingly connected world, the psychological resilience of youth is critical for safeguarding against the adverse effects of information overload and addictive behaviors. Specific Background: This article explores psychoprophylactic approaches aimed at enhancing psychological stability and mitigating negative impacts, focusing on comprehensive strategies that address the multifaceted nature of these threats. Knowledge Gap: Despite existing literature, there remains a lack of cohesive frameworks that integrate medical, educational, and psychosocial models for the prevention of addictive behavior among young individuals. Aims: This study aims to analyze current strategies and measures designed to fortify the psychological defenses of youth and to propose effective prevention frameworks. Results: The findings reveal a range of successful interventions, including programs that enhance social and personal competencies, as well as various prevention approaches that have shown promise in clinical and educational settings. Novelty: This research contributes to the existing body of knowledge by synthesizing diverse models and identifying best practices in the field of information threat prevention. Implications: The insights derived from this analysis can inform policymakers, educators, and mental health professionals in developing targeted initiatives that not only protect young individuals from information-related risks but also promote their overall psychological well-being.